The Impact of Some Vitamins and Minerals Supplements on Type 2 Diabetes (T2DM) Management: The Dietary Supplements in T2DM Management - Musafer, Karar Nadhum Jawad; Kamal Mohammed, Amera; Chobok, Ali Sabah; AL-Mousawi, Masar Riyadh Rashid; Fahrul Huyop; Tahreer M. Al-Thuwaini (Journal of Tropical Life Science, 2024)
A chronic metabolic condition, type 2 diabetes mellitus (T2DM) typically presents with hyperglycemia owing to elevated tissue insulin resistance or inadequate insulin release. In addition to the use of pharmaceutical agents and lifestyle changes for the management of T2DM, supplementation with various vitamins and minerals has also been proven to be of benefit. The objective of the present research was to establish the effectiveness of vitamin B12, vitamin C, selenium, and chromium as adjunctive therapy given over 120 days in diminishing insulin resistance. In total, 32 individuals (16 men and 16 women) living with diabetes were enrolled in the study. Fasting blood glucose (FBG), glycated hemoglobin (HbA1c), serum insulin concentrations, and homeostatic model assessment of insulin resistance (HOMA-IR) were quantified at baseline and on day 120 of supplementation. Mean FBG and HbA1c levels and insulin concentrations all decreased, i.e. 185.11 ± 22.67 mg/dL vs. 163.57 ± 19.31 mg/dL (P = 0.02), 8.47 ± 0.52% vs. 7.80 ± 0.48% (P = 0.003), and 23.15 ± 3.87 vs. 15.85 ± 1.46 (P = 0.02), respectively. HOMA-IR values remained unchanged. The association between therapy and clinical features was examined using logistic regression analysis. In the subjects with T2DM, FBG, and HbA1c levels were diminished by a factor of 2. It was concluded that vitamin and mineral supplementation was of benefit with respect to glycemic parameters. Nevertheless, high-quality evidence that supports the efficacy of such substances to improve glucose homeostasis and insulin resistance in individuals with T2DM in a clinical setting is lacking